Hydrodynamic Analysis of Combined Offshore Wind Turbine and Net Cage Under Finite-Depth Waves - Bin Wang; Mingfu Tang; Zhenqiang Jiang; Guohai Dong (Journal of Marine Science and Engineering)
Offshore wind turbines are subjected to long-term wave loads, which shorten their service life. Marine aquaculture cages are common structures in the ocean engineering field. Therefore, investigating the hydrodynamic characteristics of combined wind turbine and cage facilities under wave loads is crucial. This study employs a porous medium model to analyze the hydrodynamic behavior of a fixed wind turbine base integrated with cages under finite-depth wave conditions. First, the transmission coefficients of waves passing through cages at different positions were examined under varying cage solidity conditions. The results indicate that the cages minimally affect wave height in regions close to the cage group. Subsequently, the wave forces acting on the fixed wind turbine base behind the cages were analyzed under different solidity and wave height conditions. The variation curves of the drag coefficient and inertia coefficient were obtained for solidity values ranging from 0.3 to 0.6 and Keulegan–Carpenter (KC) numbers between 1 and 4.